2014
DOI: 10.1177/0886260514555127
|View full text |Cite
|
Sign up to set email alerts
|

Second-Generation Prisoners and the Transmission of Domestic Violence

Abstract: Adult inmates who experienced the incarceration of a parent, known as "second-generation prisoners," experience unique challenges and are at heightened risk for experiencing other adversities throughout the life span. Our study investigated one specific, and previously unexplored, type of adversity-domestic violence-within a sample of 293 incarcerated adults. We examined the relation between generation status (first-or secondgeneration prisoners), childhood exposure to domestic violence, and participation in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Parental incarceration is a risk-factor for more adverse childhood outcomes than other types of parental separation (Murray & Farrington, 2005). However, the scope of these effects has been mostly limited to adult criminological outcomes (e.g., arrests, violent behavior; Huebner & Gustafson, 2007;Muftic et al, 2016;Will et al, 2016). The present study builds on this prior research, showing that the effects of parental incarceration during childhood are associated with empathy deficits for daughters into adulthood.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Parental incarceration is a risk-factor for more adverse childhood outcomes than other types of parental separation (Murray & Farrington, 2005). However, the scope of these effects has been mostly limited to adult criminological outcomes (e.g., arrests, violent behavior; Huebner & Gustafson, 2007;Muftic et al, 2016;Will et al, 2016). The present study builds on this prior research, showing that the effects of parental incarceration during childhood are associated with empathy deficits for daughters into adulthood.…”
Section: Discussionmentioning
confidence: 72%
“…It has been suggested that there is an inter-generational influence of parental incarceration on children, which carries through into adulthood Will, Loper, & Jackson, 2016). However, past studies have not examined the long-term effect of parental incarceration on empathy among female offspring from both offender and non-offender samples.…”
Section: The Current Studymentioning
confidence: 99%
“…This is also related to the age of pregnant women; the incidence of postpartum depression is most common in pregnant women who are too young or too old. Pregnant women of suitable age in pregnancy will be more adaptable and not cause easy sadness, because of the productive age (Henry & Powell, 2016;Will et al, 2016). A harmonious household situation must also be established by each family member, both husband and wife, so that the incidence of violence against women can be prevented and reduced (Michau et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to family-of-origin violence has been associated with IPV perpetration or violence outside during adulthood (Machisa, Christofides, & Jewkes, 2016; Milaniak & Widom, 2015; Song, Wenzel, Kim, & Nam, 2017; Will, Loper, & Jackson, 2016). A meta-analysis about the intergenerational transmission of physical abuse showed that the relative risk of abuse transmission was 12.6 (95% confidence interval [CI] = [1.82, 87.2]) (Ertem, Leventhal, & Dobbs, 2000).…”
mentioning
confidence: 99%